Polymorphisms within Autophagy-Related Genes as Susceptibility Biomarkers for Multiple Myeloma: A Meta-Analysis of Three Large Cohorts and Functional Characterization - Clavero, Esther; Sanchez-Maldonado, José Manuel; Macauda, Angelica; Ter Horst, Rob; Sampaio-Marques, Belém; Jurczyszyn, Artur; Clay-Gilmour, Alyssa; Stein, Angelika; Hildebrandt, Michelle A T; Weinhold, Niels; Buda, Gabriele; García-Sanz, Ramón; et al. (International journal of molecular sciences, 2023)
Multiple myeloma (MM) arises following malignant proliferation of plasma cells in the bone marrow, that secrete high amounts of specific monoclonal immunoglobulins or light chains, resulting in the massive production of unfolded or misfolded proteins. Autophagy can have a dual role in tumorigenesis, by eliminating these abnormal proteins to avoid cancer development, but also ensuring MM cell survival and promoting resistance to treatments. To date no studies have determined the impact of genetic variation in autophagy-related genes on MM risk. We performed meta-analysis of germline genetic data on 234 autophagy-related genes from three independent study populations including 13,387 subjects of European ancestry (6863 MM patients and 6524 controls) and examined correlations of statistically significant single nucleotide polymorphisms (SNPs; p < 1 × 10-9) with immune responses in whole blood, peripheral blood mononuclear cells (PBMCs), and monocyte-derived macrophages (MDM) from a large population of healthy donors from the Human Functional Genomic Project (HFGP). We identified SNPs in six loci, CD46, IKBKE, PARK2, ULK4, ATG5, and CDKN2A associated with MM risk (p = 4.47 × 10-4-5.79 × 10-14). Mechanistically, we found that the ULK4rs6599175 SNP correlated with circulating concentrations of vitamin D3 (p = 4.0 × 10-4), whereas the IKBKErs17433804 SNP correlated with the number of transitional CD24+CD38+ B cells (p = 4.8 × 10-4) and circulating serum concentrations of Monocyte Chemoattractant Protein (MCP)-2 (p = 3.6 × 10-4). We also found that the CD46rs1142469 SNP correlated with numbers of CD19+ B cells, CD19+CD3- B cells, CD5+IgD- cells, IgM- cells, IgD-IgM- cells, and CD4-CD8- PBMCs (p = 4.9 × 10-4-8.6 × 10-4) and circulating concentrations of interleukin (IL)-20 (p = 0.00082). Finally, we observed that the CDKN2Ars2811710 SNP correlated with levels of CD4+EMCD45RO+CD27- cells (p = 9.3 × 10-4). These results suggest that genetic variants within these six loci influence MM risk through the modulation of specific subsets of immune cells, as well as vitamin D3-, MCP-2-, and IL20-dependent pathways.
Keywords: imunoglobulin M; Immunoglobulin M; autofagie; biologické markery; Leukocytes, Mononuclear; lidé; mnohočetný myelom; Multiple Myeloma; Autophagy; Humans; Biomarkers; leukocyty mononukleární